IMPLEMENTASI GERAKAN SATU RUMAH SATU JUMANTIK (G1R1J) MEWUJUDKAN LINGKUNGAN BEBAS DEMAM BERDARAH DENGUE - Widiyanto, Puguh; Widyantoro, Tri; Ulva, Syarifatul; Ningrum, Meiliana Purnama; Safitri, Nita Ana (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2021)
Implementation of activities one house one larva monitors (G1R1J) is a community-based empowerment program for the eradication of mosquito nests to prevent the reproduction of the Aedes Agepty vector mosquito that causes Dengue Hemorrhagic Fever (DHF). The case fatality rate in the first semester of 2020 was ranked third in Central Java (6.67%), far exceeding the national standard of less than 2%. Although the incidence of dengue fever at the Mertoyudan Health Center has a tendency to decline in the first semester of 2020, entering the rainy season requires public vigilance for the emergence of dengue cases. Santan Village RT 06 RW 02, Sumberejo sub-district, the working area of Mertoyudan Health Center has 152 people with 47 family heads, inseparable from the importance of preventing DHF, being the target of community service by implementing G1R1J. The results obtained after the completion of the activity obtained increased knowledge, attitudes and behavior of the community.